Smoking cessation in smoke-free prisons: a grounded theory study. Issue 4 (19th December 2016) - Djachenko, Ashleigh; St John, Winsome; Mitchell, Creina
Abstract : Purpose: Prisoners are vulnerable to tobacco addiction and have a smoking prevalence significantly higher than that of the general community. The context of this study was the implementation of a "smoke-free prisons" policy, which imposed forced smoking cessation onto the Queensland, Australian prison population. The study asked the question: "What are the psychosocial processes in which male prisoners engage during smoking cessation in a smoke-free environment?" Design/methodology/approach: Qualitative interviews were conducted with 15 prisoners in South-east Queensland smoke-free correctional centres. Grounded theory methodology was applied to construct a theory of the processes of smoking cessation. Findings: The constructed theory was named Engaging with Quitting. In this model, prisoners proceed through a cycle of evaluations, adjustments and reflections on their reality as related to the smoke-free prison. The study gives first-hand accounts of the prisoners' use (and abuse) of nicotine replacement therapy. Three personality typologies emerged from the data: The Angry Smoker, the Shifting Opportunist and the Optimistic Quitter. Research limitations/implications: This qualitative study makes no claim of generalisability and cannot be taken to represent all prisoners. Females, youths and culturally diverse prisoners were not represented in the sample. Practical implications: Smoking cessation in prisons must be recognised as an ongoing process, rather than a discrete event. A coordinated approach between custodial and health authorities is required to minimise maladaptive coping strategies. Originality/value: This study provides a descriptive account of the processes prisoners undertake during involuntary smoking cessation and has described the manner in which prisoners manufacture home-made tobacco from nicotine patches. The study has produced an original theory named Engaging with Quitting.